Pengaruh Desain Dan Harga Produk Terhadap Minat Pembelian Kosmetik Korea Merek Moko-Moko - Suhaila Husna Samosir (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara, 2022)
This study aims to determine whether the product design and prices affect the purchase interest of Korean instant cosmetics with the Moko brand. This study uses a descriptive method through a quantitative approach with data analysis techniques used, namely multiple linear regression and hypothesis testing (T-test and F-test). . The population in this study were 500 people in Dusun IV Bangun Sari Baru Village, Tanjung Morawa District. This study uses the Slovin formula and purposive sampling in determining samples with an error tolerance of 15%, the number of samples obtained is as many as 40 samples. The results of the partial test research (t-test) show that the t value of the Design variable (X1) is greater than the t table value, namely 3.573 2.026 with a significance of 0.001 0.05, then Ho is rejected and Ha is accepted so that the variable X1 has a contribution to the variable Y. While for the Product Price variable (X2), the results show that the Product Price has a positive effect on Purchase Interest, this is indicated by the t value is greater than the t table value or 2.440 2.036 with a significance of 0.020 0.05, then Ho rejected and Ha accepted. While the results of the simultaneous test (F-test) of the two independent variables on the dependent variable, the results showed that the value of fcount was 23.153 3.25 with a significance of 0.000 0.05. The coefficient of determination is 0.556 or 55.6%, this means that the Design variable (X1) and the Product Price variable (X2) have an effect of 55.6% on the Purchase Interest variable (Y) Korean Instant Cosmetics with Moko-Moko Brand in Dusun IV Bangun Sari Village Community. Baru Tanjung Morawa District, while the rest is influenced by other variables outside this study.